Systematic Review of Membrane Components of Gram-Positive Bacteria Responsible as Pyrogens for Inducing Human Monocyte/Macrophage Cytokine Release - Hartung, Thomas; Rockel, Christoph (Frontiers in Pharmacology, 2012)
Fifty years after the elucidation of lipopolysaccharides (LPS, endotoxin) as the principal structure of Gram-negative bacteria activating the human immune system, its Gram-positive counterpart is still under debate. Pyrogen tests based on the human monocyte activation have been validated for LPS detection as an alternative to the rabbit test and, increasingly, the limulus amebocyte lysate test. For full replacement, international validations with non-endotoxin pyrogens are in preparation. Following evidence-based medicine approaches, a systematic review of existing evidence as to the structural nature of the Gram-positive pyrogen was undertaken. For the three major constituents suggested, i.e. peptidoglycan, lipoteichoic acids (LTA), and bacterial lipoproteins, the questions to be answered and a search strategy for relevant literature was developed, starting in MedLine. The evaluation was based on the Koch-Dale criteria for a mediator of an effect. A total of 380 articles for peptidoglycan, 391 for lipoproteins, and 285 for LTA were retrieved of which 12, 8 and 24, respectively, fulfilled inclusion criteria. The compiled data suggest that for peptidoglycan two Koch-Dale criteria are fulfilled, four for LTA, and two for bacterial lipoproteins. In conclusion, based on the best currently available evidence, LTA is the only substance that fulfils all criteria. LTA has been isolated from a large number of bacteria, results in cytokine release patterns inducible also with synthetic LTA. Reduction in bacterial cytokine induction with an inhibitor for LTA was shown. However, this systematic review cannot exclude the possibility that other stimulatory compounds complement or substitute for LTA in being the counterpart to LPS in some Gram-positive bacteria.